A method for reconstructing and synergistically detoxifying magnesium olivine based on waste incineration fly ash

CN122209788BActive Publication Date: 2026-11-03ZHEJIANG UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610548429.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-04-23
Publication Date
2026-11-03
Estimated Expiration
2046-04-23

AI Technical Summary

Technical Problem

现有技术难以同时实现垃圾焚烧飞灰的无害化处置、镁橄榄石高效活化及低成本CO2矿化,且存在高能耗、复杂工艺和二次污染问题。

Method used

By controlling the chloride content in fly ash through component detection, and employing a two-stage heat treatment and rapid cooling method, the low-melting-point chloride in fly ash is used as a mass transfer medium to promote the reconstruction of magnesium olivine into highly active dicalcium silicate and magnesium oxide, thereby achieving detoxification and CO2 mineralization of fly ash.

Benefits of technology

It achieves deep detoxification and heavy metal stabilization of fly ash, reduces process costs, simplifies process flow, avoids the generation of high-salt wastewater, and improves CO2 mineralization efficiency, making it suitable for large-scale industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122209788B_ABST
    Figure CN122209788B_ABST
Patent Text Reader

Abstract

The application discloses a method for reconstructing and synergistically detoxifying magnesium olivine based on waste incineration fly ash, and relates to the technical field of solid waste treatment.The application creates a low-cost innovative mode of "waste treatment with waste", directly uses hazardous waste incineration fly ash as a chemical activator of natural magnesium olivine, and does not need to additionally add expensive reagents such as strong acid, strong base or ammonium salt.Through early component detection and regulation of the content of chloride salt in the fly ash to 20%-25%, while limiting the content of inert components such as SiO2, Al2O3 and Fe2O3, the originally harmful chloride salt in the fly ash is converted into a key molten salt medium required for subsequent high-temperature reconstruction, which significantly reduces the preparation cost of magnesium olivine activation and CO2 mineralization materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid waste treatment technology, specifically to a method for synergistic detoxification based on magnesium olivine reconstruction driven by fly ash from waste incineration. Background Technology

[0002] Fly ash from municipal solid waste incineration is a solid pollutant generated during the incineration of municipal solid waste. Due to its high content of highly toxic dioxins, heavy metals (such as Pb, Cd, Cr, and Zn), and large amounts of soluble chloride salts, it is listed in the "National Hazardous Waste List." Currently, the mainstream disposal methods for fly ash include landfill after cement solidification / stabilization, high-temperature melting, and co-processing in cement kilns. However, solidification and landfilling pose long-term environmental risks, as heavy metals may leach out under acidic conditions; high-temperature melting has extremely high energy consumption, making large-scale promotion difficult; and co-processing in cement kilns has strict limitations on the chloride content in fly ash (usually requiring a chloride content of <1%), necessitating water washing pretreatment, which not only generates secondary pollution from high-salt wastewater but also increases process costs.

[0003] On the other hand, forsterite (Mg2SiO4), as a natural silicate mineral, has attracted attention in the field of CO2 mineralization and storage due to its rich content of alkaline magnesium components. Theoretically, forsterite can convert CO2 into stable carbonate (MgCO3) through carbonation. However, natural forsterite has a highly polymerized silicon-oxygen bond network ([SiO4] tetrahedral structure), which is extremely chemically stable and hardly reacts with CO2 at room temperature and pressure. Existing activation techniques usually employ strong acid (such as sulfuric acid or hydrochloric acid) leaching or high-temperature (>600℃) thermal activation combined with ammonium salts to destroy its crystal structure and extract magnesium ions. For example, literature reports the use of ammonium sulfate mixed with forsterite for roasting, followed by precipitation with ammonia water to prepare magnesium hydroxide. However, these methods have the following prominent problems: (1) they consume a large amount of chemical reagents, are costly, and the preparation process of acid / ammonium salts itself has significant carbon emissions; (2) the process flow is complex, involving multiple steps such as acid leaching, separation, and precipitation; (3) the final carbonization product has limited activity, and the CO2 mineralization efficiency is far lower than the theoretical value.

[0004] In recent years, researchers have attempted to co-process fly ash with natural minerals. However, existing technologies mostly focus on preparing building materials from fly ash with aluminosilicate materials such as slag and fly ash, aiming to solidify heavy metals rather than recover or utilize the minerals' activity. In these processes, the high chloride content (typically 10%–30%) in fly ash is considered a harmful component, as it can cause steel corrosion in building materials or generate volatile chlorine compounds. Therefore, existing processes often require an additional water washing and dechlorination step, leading to increased costs and wastewater problems. Furthermore, products from fly ash treated at high temperatures (>1000℃) exhibit poor resource utilization potential and ineffective heavy metal solidification.

[0005] In summary, developing a synergistic technology that can simultaneously achieve the harmless disposal of fly ash, efficient activation of magnesium olivine, and low-cost preparation of CO2 mineralization materials is of significant environmental and economic importance. How to avoid the use of expensive reagents such as strong acids and alkalis, mitigate the negative interference of chloride salts in fly ash, or even transform them into beneficial factors, and achieve deep degradation of dioxins and simultaneous stabilization of heavy metals are urgent technical challenges to be solved in this field. Summary of the Invention

[0006] To address the aforementioned shortcomings of existing technologies, this invention provides a method for synergistic detoxification based on magnesium olivine remodeling driven by waste incineration fly ash.

[0007] To achieve the above-mentioned objectives, the technical solution adopted by this invention is as follows: A method for synergistic detoxification based on forsterite reconstruction driven by waste incineration fly ash is provided, which adopts the following specific steps: S1: Conduct component analysis on the fly ash from waste incineration, and add calcium oxide according to the component analysis results so that the total mass fraction of chloride salts in the mixture after addition is 20%~25%, and the total mass fraction of chloride-free SiO2, Al2O3 and Fe2O3 is not greater than 10%; By controlling the composition and CaO content in the mixed system through preliminary component analysis, the formation of inert aluminosilicate / ferrite minerals that are difficult to carbonate during subsequent high-temperature processes is strictly limited, thus inhibiting their formation at the source. Simultaneously, 20-30% of chloride salts in the fly ash are retained and controlled as a key reaction medium.

[0008] S2: Mix the mixture with forsterite at a calcium to magnesium molar ratio of 1.5 to 2:1 to obtain the target compound material. Grind the target compound material to obtain the compound powder. S3: The compounded powder is subjected to a two-stage heat treatment. The first stage of heat treatment is: heat treatment at 900℃ for 0.5~1h; the second stage of heat treatment is: after the first stage of heat treatment, the temperature is directly raised to 1100~1200℃ and heat treated for 2~3h, and then cooled down by rapid air cooling. This completes the reconstruction of magnesium olivine to obtain air-fixed carbon material and achieves the detoxification of fly ash from waste incineration.

[0009] Under the combined action of high temperature and chloride salts, volatile heavy metals (such as Pb, Cd, and Zn) in fly ash are converted into gaseous metal chlorides and discharged with the flue gas (they can be efficiently collected and recovered through tail gas condensation or dust removal systems); while non-volatile heavy metal elements are captured by the crystal lattice and firmly stabilized in the crystal structure of newly formed dicalcium silicate. A nitrogen atmosphere suppresses and stabilizes the low-toxicity Cr. 3+ It is oxidized into Cr, which is easily leached and highly toxic. 6+ This significantly reduces its leaching toxicity.

[0010] Furthermore, in step S2, the target compatible material is ground to an average particle size of 10~30μm.

[0011] Furthermore, the grinding process employs a planetary ball mill for dry ball milling at a speed of 600 rpm, a ball-to-material mass ratio of 5-10:1, and a milling time of 1 hour.

[0012] Furthermore, in step S3, the heating rate of the first heat treatment stage to 900°C is 20°C / min.

[0013] In the first stage of heat treatment, low-melting-point chloride salts such as NaCl, KCl, and CaCl2 in the fly ash gradually melt, forming a liquid molten salt phase between the material particles. This molten salt phase not only serves as an excellent heat and mass transfer medium to wet the mineral particles and significantly reduce the apparent activation energy of the solid-phase reaction, but also, under this high-temperature environment, the inherent persistent organic pollutants in the fly ash, such as dioxins, undergo complete molecular chain breakage and thermal degradation, achieving deep detoxification of organic pollutants. Furthermore, the nitrogen atmosphere greatly inhibits the regeneration of dioxins.

[0014] Furthermore, in step S3, the heating rate of the second heat treatment to 1100~1200℃ is 10℃ / min.

[0015] During the second stage of heat treatment, under the enhanced mass transfer effect of the molten salt phase, a large amount of free CaO in the fly ash diffuses into the lattice of forsterite (Mg2SiO4). Due to the binding energy of the Ca-O bond and the lattice fit, Ca... 2+ Capable of efficiently attacking and breaking the Mg-O-Si network, removing the original Mg 2+ Displaced from the crystal lattice, it promotes thermochemical reconstruction of the mineral phase, and directionally transforms it into dicalcium silicate (Ca2SiO4) and free magnesium oxide (MgO), which have low crystallinity and extremely high reactivity.

[0016] Furthermore, both stages of heat treatment are carried out in a nitrogen atmosphere. The nitrogen flow rate is based on the feed mass of the compounded powder. The nitrogen flow rate in the first stage is 1~5 L / (min·kg), and the nitrogen flow rate in the second stage is 10~20 L / (min·kg).

[0017] Furthermore, the rapid air cooling rate is ≥50°C / minute.

[0018] After high-temperature reconstruction, the newly formed highly active phases (including MgO and Ca2SiO4) are prone to secondary reactions during slow cooling, transforming into inert, non-active phases such as magnesium aluminosilicate. However, the rapid air cooling (≥50℃ / minute) employed in this invention can instantly "freeze" the highly active amorphous or microcrystalline structures formed at high temperatures.

[0019] Furthermore, the air-fixed carbon material is ground to an average particle size of 5-10 micrometers.

[0020] Furthermore, the air-fixed carbon material was ground using a planetary ball mill for dry ball milling at a speed of 600 rpm, a ball-to-material mass ratio of 5~10:1, and a milling time of 2 hours.

[0021] Fine dry ball milling not only further reduces the particle size to 5-10 micrometers, but also creates a large number of surface lattice defects and broken bonds, exposing more Ca / Mg active sites, ultimately obtaining air-fixed carbon materials with excellent carbonization kinetics.

[0022] The beneficial effects of this invention are as follows: This invention pioneers a low-cost, innovative "waste-to-waste" model, directly utilizing fly ash from hazardous waste incineration as a chemical activator for natural magnesium olivine, without the need for expensive reagents such as strong acids, strong alkalis, or ammonium salts. By pre-processing component analysis and controlling the chloride content in the fly ash to 20%–25%, while limiting the content of inert components such as SiO2, Al2O3, and Fe2O3, the originally harmful chloride in the fly ash is transformed into a key molten salt medium required for subsequent high-temperature reconstruction, significantly reducing the preparation cost of magnesium olivine activation and CO2 mineralization materials.

[0023] During this process, persistent organic pollutants such as dioxins in fly ash undergo complete thermal degradation during the first stage of 900℃ heat treatment, while the nitrogen atmosphere effectively inhibits the low-temperature regeneration of dioxins. For heavy metals, volatile Pb, Cd, and Zn are converted into gaseous metal chlorides and discharged with the flue gas, allowing for efficient recovery. Non-volatile heavy metals are captured by the crystal lattice and stably dissolved in the newly formed dicalcium silicate crystal structure, and the nitrogen atmosphere prevents the degradation of Cr... 3+ It is oxidized into highly toxic and easily leached Cr. 6+ This achieves deep synergistic detoxification, and the reconstructed products are completely free from hazardous waste properties, resulting in high environmental safety.

[0024] Furthermore, this invention transforms the chloride salts commonly found in fly ash from "harmful components" into "functional media." The low-melting-point chloride salts melt to form a liquid molten salt phase, which significantly enhances the heat and mass transfer processes in the solid-phase reaction. This significantly reduces the apparent activation energy and reaction temperature required for the reconstruction of calcium / magnesium minerals. The reconstruction temperature used is only 1100–1200°C, which is lower than that of traditional high-temperature melting processes.

[0025] This invention employs a two-stage heat treatment process (900℃ pre-activation + 1100-1200℃ reconstruction). Under molten salt strengthening, CaO in fly ash directionally attacks the Mg-O-Si network of forsterite, transforming it into highly active dicalcium silicate and free magnesium oxide. Subsequently, rapid air cooling at ≥50℃ / min instantly "freezes" the highly active amorphous or microcrystalline structure formed at high temperatures, avoiding the formation of inert phases during slow cooling. Combined with subsequent fine grinding to 5-10 micrometers and the introduction of numerous surface defects, the resulting air-fixed carbon material is rich in active Ca / Mg sites, exhibiting excellent CO2 mineralization and storage kinetics.

[0026] The entire process simultaneously completes fly ash detoxification and magnesium olivine activation and reconstruction in the same thermal process, eliminating the need for pre-dechlorination of fly ash by water washing, thus avoiding the generation of high-salt wastewater. The process is simple, highly efficient, and suitable for large-scale industrial applications. Attached Figure Description

[0027] Figure 1 The images show the XRD patterns of the air-fixed carbon materials prepared in Examples 1-3. Figure 2 SEM-EDS images of the air-fixed carbon materials prepared in Examples 1-3; Figure 3 The XRD patterns are for the solid samples prepared in Comparative Examples 1 and 2. Detailed Implementation

[0028] The specific embodiments of the present invention are described below to enable those skilled in the art to understand the present invention. However, it should be understood that the present invention is not limited to the scope of the specific embodiments. For those skilled in the art, various changes are obvious as long as they are within the spirit and scope of the present invention as defined and determined by the appended claims. All inventions utilizing the concept of the present invention are protected.

[0029] In this embodiment of the invention, the fly ash used was taken from a waste incineration plant in Zhejiang Province. The elemental composition (mass percentage) of the original fly ash is shown in Table 1 below. Table 1

[0030] The heavy metal leaching concentrations (mg / L) of the original fly ash under the HJ / T 557-2010 standard are shown in Table 2 below, and the dioxin toxicity equivalent concentration (ng-TEQ / kg) is 175.0.

[0031] Table 2

[0032] Example 1 A method for synergistic detoxification based on forsterite reconstruction driven by waste incineration fly ash, the specific steps of which are as follows: Based on the test results, 16.54% CaO per unit mass of fly ash was added to adjust the composition of the fly ash, thereby satisfying the following conditions: a) The total mass fraction of chloride in fly ash after adding CaO is controlled at 25%; b) The total mass fraction of SiO2, Al2O3 and Fe2O3 in the fly ash after CaO addition is ≤10% based on chloride-free base.

[0033] The adjusted fly ash and forsterite were mixed at a calcium to magnesium molar ratio of 1.5:1 to obtain the target blended material, i.e., 1 kg of fly ash was mixed with 0.361 kg of forsterite. The target blended material was then subjected to dry ball milling pretreatment using a planetary ball mill. The operating conditions were set as follows: ball milling speed 600 rpm, ball-to-material mass ratio 5:1, ball milling time 1 h, and the average particle size of the mixture was controlled to be 10~30 micrometers to obtain the ball milling pretreated mixture, i.e., the blended powder.

[0034] The pre-treated ball-milled mixture is placed in a nitrogen atmosphere furnace for segmented heat treatment. Both stages of heat treatment are carried out under a nitrogen atmosphere, with the nitrogen flow rate based on the feed mass of the formulated powder. This allows the fly ash calcium-based components to drive a thermochemical remodeling reaction in the magnesium olivine, specifically including: a) First stage: Heat to 900℃ at a heating rate of 20℃ / min and hold for 1 hour, with nitrogen flow rate set to 5L / (min·kg); b) Second stage: Continue heating to 1200℃ at a heating rate of 10℃ / min and hold for 2h, with nitrogen flow rate set to 10L / (min·kg); After the segmented heat treatment, the high-temperature product was removed from the reactor and cooled down by rapid air cooling. The cooled reconstituted product was then ball-milled using a planetary ball mill. The ball milling conditions were set as follows: ball milling speed 600 rpm, ball-to-material mass ratio 10:1, and ball milling time 2 hours, to obtain air-fixed carbon material with a particle size of 5-10 micrometers.

[0035] Example 2 A method for synergistic detoxification based on forsterite reconstruction driven by waste incineration fly ash, the specific steps of which are as follows: Add 29.5% calcium oxide per unit fly ash mass to the fly ash from waste incineration; mix the regulated fly ash with forsterite at a calcium to magnesium molar ratio of 2:1 to obtain the target blended material, i.e., 0.408 kg of forsterite per 1 kg of fly ash; then perform dry ball milling pretreatment on the target blended material using a planetary ball mill, with the operating conditions set as follows: ball milling speed 600 rpm, ball-to-material mass ratio 10:1, and ball milling time 1 h, to obtain a ball milling pretreated mixture with an average particle size of 10-30 micrometers.

[0036] The pre-treated ball-milled mixture is placed in a nitrogen atmosphere furnace for segmented heat treatment. Both stages of heat treatment are carried out under a nitrogen atmosphere, with the nitrogen flow rate based on the feed mass of the formulated powder. This allows the fly ash calcium-based components to drive a thermochemical remodeling reaction in the magnesium olivine, specifically including: a) First stage: Heat to 900℃ at a heating rate of 20℃ / min and hold for 0.5h, with nitrogen flow rate set to 1L / (min·kg); b) Second stage: Continue heating to 1100℃ at a heating rate of 10℃ / min and hold for 3h, with nitrogen flow rate set to 20L / (min·kg); After the segmented heat treatment, the high-temperature product was taken out of the reactor and cooled down by rapid air cooling. The cooled reconstituted product was then ball-milled using a planetary ball mill. The ball milling conditions were set as follows: ball milling speed 600 rpm, ball-to-material mass ratio 5:1, and ball milling time 2 hours, to obtain air-fixed carbon material with a particle size of 5-10 micrometers.

[0037] Example 3 A method for synergistic detoxification based on forsterite reconstruction driven by waste incineration fly ash, the specific steps of which are as follows: Add 45.7% calcium oxide per unit fly ash mass to the fly ash from waste incineration; mix the adjusted fly ash with forsterite at a calcium to magnesium molar ratio of 1.75:1 to obtain the target blended material, i.e., 0.456 kg of forsterite per 1 kg of fly ash; then perform dry ball milling pretreatment on the target blended material using a planetary ball mill, with the operating conditions set as follows: ball milling speed 600 rpm, ball-to-material mass ratio 7.5:1, and ball milling time 1 h, to obtain a ball milling pretreated mixture with an average particle size of 10-30 micrometers.

[0038] The pre-treated ball-milled mixture is placed in a nitrogen atmosphere furnace for segmented heat treatment. Both stages of heat treatment are carried out under a nitrogen atmosphere, with the nitrogen flow rate based on the feed mass of the formulated powder. This allows the fly ash calcium-based components to drive a thermochemical remodeling reaction in the magnesium olivine, specifically including: a) First stage: Heat to 900℃ at a heating rate of 20℃ / min and hold for 0.75h, with nitrogen flow rate set to 3L / (min·kg); b) Second stage: Continue heating to 1150℃ at a heating rate of 10℃ / min and hold for 2.5h, with the nitrogen flow rate set to 15L / (min·kg); After the segmented heat treatment, the high-temperature product was taken out of the reactor and cooled down by rapid air cooling. The cooled reconstituted product was then ball-milled using a planetary ball mill. The ball milling conditions were set as follows: ball milling speed 600 rpm, ball-to-material mass ratio 7.5:1, and ball milling time 2 hours, to obtain air-fixed carbon material with a particle size of 5-10 micrometers.

[0039] Example 4 The air-fixed carbon materials prepared in Examples 1-3 were subjected to X-ray diffraction analysis, and the results were as follows: Figure 1 The XRD patterns shown also illustrate the XRD patterns obtained by scanning electron microscopy and energy dispersive spectroscopy (EDS) analysis of the air-fixed carbon materials prepared in Examples 1-3. Figure 2 The SEM-EDS diagram shown below, in which, Figure 2 In the image, 'a' represents the SEM-EDS image of the air-fixed carbon material prepared in Example 1. Figure 2 b in the figure is the SEM-EDS image of the air-fixed carbon material prepared in Example 2; Figure 2 c in the image represents the SEM-EDS image of the air-fixed carbon material prepared in Example 3; and Figure 2 C2S in the formula is dicalcium silicate; Depend on Figure 1 and Figure 2 It is known that the method of the present invention has successfully prepared reconstructed minerals rich in dicalcium silicate (Ca2SiO4) and magnesium oxide (MgO).

[0040] Meanwhile, the heavy metal leaching concentration (mg / L) and dioxin toxicity equivalent concentration (ng-TEQ / kg) of the air-fixed carbon materials prepared in Examples 1-3 were also tested, and the results are shown in Table 3 below; Table 3

[0041] As shown in Table 3, the heavy metal leaching toxicity and dioxin toxicity equivalent of the reconstituted products prepared by the method of the present invention were significantly reduced, which fully demonstrates that the method of the present invention can exert a highly efficient synergistic detoxification effect on heavy metals and dioxins in fly ash.

[0042] To verify the specificity of the method of the present invention, a comparative example was also provided, specifically: Comparative Example 1 The difference between this embodiment and Embodiment 1 is that: the fly ash is acid-washed to remove chloride salts and acid-soluble calcium, retaining only the calcium sulfate component in the fly ash; the acid-washed fly ash is mixed with forsterite at a calcium-to-magnesium ion molar ratio of 1.5:1, and 5% Na₂SO₄ by weight of the raw materials is added as a flux. The sample is placed in a muffle furnace at 1200 degrees Celsius for 4 hours, and then allowed to cool naturally to obtain a solid sample.

[0043] Comparative Example 2 The difference between this embodiment and Embodiment 1 is that the two-step heat treatment is replaced by a one-step heat treatment, directly raising the temperature to 1200 degrees Celsius and holding it for 2 hours at a heating rate of 10°C / minute.

[0044] XRD analysis was performed on the solid samples prepared in Comparative Example 1 and Comparative Example 2, and the results are as follows: Figure 3 As shown, by Figure 3 It can be seen that a large number of non-target minerals were generated in the products of Comparative Example 1 and Comparative Example 2, and the peak of the target mineral MgO was significantly smaller than that of Example 1.

Claims

1. A method for synergistic detoxification based on magnesium olivine remodeling driven by waste incineration fly ash, characterized in that, The specific steps are as follows: S1: Conduct component analysis on the fly ash from waste incineration, and add calcium oxide according to the component analysis results so that the total mass fraction of chloride salts in the mixture after addition is 20%~25%, and the total mass fraction of chloride-free SiO2, Al2O3 and Fe2O3 is not greater than 10%; S2: Mix the mixture with forsterite at a calcium to magnesium molar ratio of 1.5 to 2:1 to obtain the target compound material. Grind the target compound material to obtain the compound powder. S3: The compounded powder is subjected to a two-stage heat treatment. The first stage of heat treatment is: heat treatment at 900℃ for 0.5~1h; the second stage of heat treatment is: after the first stage of heat treatment, the temperature is directly raised to 1100~1200℃ and heat treated for 2~3h, and then cooled down by rapid air cooling. This completes the reconstruction of magnesium olivine to obtain air-fixed carbon material and achieves the detoxification of fly ash from waste incineration.

2. The method for synergistic detoxification based on magnesium olivine remodeling driven by waste incineration fly ash according to claim 1, characterized in that, In step S2, the target compatible materials are ground to an average particle size of 10~30μm.

3. The method for synergistic detoxification based on magnesium olivine remodeling driven by waste incineration fly ash according to claim 2, characterized in that, The grinding was carried out by dry ball milling using a planetary ball mill at a speed of 600 rpm, a ball-to-material mass ratio of 5~10:1, and a grinding time of 1 hour.

4. The method for synergistic detoxification based on magnesium olivine remodeling driven by waste incineration fly ash according to claim 1, characterized in that, In step S3, the heating rate of the first heat treatment stage to 900℃ is 20℃ / min.

5. The method for synergistic detoxification based on magnesium olivine remodeling driven by waste incineration fly ash according to claim 4, characterized in that, In step S3, the heating rate of the second heat treatment stage, which raises the temperature to 1100~1200℃, is 10℃ / min.

6. The method for synergistic detoxification based on magnesium olivine remodeling driven by waste incineration fly ash according to claim 1, characterized in that, In the two-stage heat treatment, both processes are carried out under a nitrogen atmosphere. The nitrogen flow rate is based on the feed mass of the compounded powder. The nitrogen flow rate in the first stage is 1~5 L / (min·kg), and the nitrogen flow rate in the second stage is 10~20 L / (min·kg).

7. The method for synergistic detoxification based on magnesium olivine remodeling driven by waste incineration fly ash according to claim 1, characterized in that, Rapid air cooling has a cooling rate of ≥50℃ / minute.

8. The method for synergistic detoxification based on magnesium olivine remodeling driven by waste incineration fly ash according to claim 1, characterized in that, The air-fixed carbon material was also ground to an average particle size of 5-10 micrometers.

9. The method for synergistic detoxification based on magnesium olivine remodeling driven by waste incineration fly ash according to claim 8, characterized in that, The air-fixed carbon material was ground using a planetary ball mill for dry ball milling at a speed of 600 rpm, a ball-to-material mass ratio of 5 to 10:1, and a milling time of 2 hours.

Citation Information

Patent Citations

  • Process for storing carbon dioxide in flue gas by utilizing brucite

    CN102247753A

  • Melting separation treatment method for heavy metal in waste incineration fly ash

    CN118109691A